Vascular plant communities in the polar desert of Alert (Ellesmere Island, Canada): Establishment of a baseline reference for the 21st century. Issue 3 (2nd October 2021) - Desjardins, Émilie; Lai, Sandra; Payette, Serge; Vézina, François; Tam, Andrew; Berteaux, Dominique
ABSTRACT: The startling warming of the Arctic is driving important environmental changes, but vegetation responses have been spatially heterogeneous and difficult to predict. In this context, establishing new ecological baselines and initiating monitoring schemes are essential. We conducted systematic plot-based surveys in the polar desert surrounding Alert (Nunavut, Canada). We aimed at (1) identifying distinct plant communities, (2) characterizing community attributes, including diversity and abundance, as well as environmental variables associated with each community, and (3) establishing a georeferenced baseline with permanent field markers allowing robust re-surveying. We used hierarchical clustering to categorize cover values of vascular plant species, cryptogams, and ground substrates from 1, 320 quadrats (1 m 2 each) surveyed in 264 vegetation plots. Five plant communities were identified, with one community associated with each of the barren and mesic habitats, and three communities associated with wetlands. The mean biotic covers were generally higher at Alert (13–98%) compared to other polar deserts in the Canadian Arctic Archipelago. A total of 250 quadrats from 50 vegetation plots were permanently marked, and a database describing all plots is available online. This study improves our understanding of High-Arctic plant communities and establishes an important vegetation monitoring reference at the northernmost permanently inhabited settlement on Earth.